Academic achievements : An evaluation on Grade point average among selected student athletes on-semester of competition and non-semester competition - Nocon, Evan C.; Socrates, Jayson P.;Dagsa, Jerico A.;Baccay, Mike Lester M.;Valenzuela, Patrick R. (Manila : National University, 2018)
This study aimed to determine the evaluation on grade point average among selected student-athletes on-semester of competition and non-semester of competition of National University whom is currently enrolled in an academic program during the school year 2017-2018.
Table of Contents -- Chapter 1. The Problem and its Background -- Chapter 2. Review of Related Literature and Studies -- Chapter 3. Methods and Procedure -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendations -- Bibliography -- Appendices.
Research Method: Qualitative Research Design
Includes bibliographical references.